A noteworthy issue: microbiome data variation depending on sampling methods in skin microecology studies in acne vulgaris patients - De-Tian Xu; De-Tian Xu; Qi Chen; Jia-Yi Yang; Guo-Rong Yan; Ling-Lin Zhang; Xiao-Jing Liu; Pei-Ru Wang; Jia Liu; Xiu-Li Wang (Frontiers in Immunology)
IntroductionSkin microecology significantly affects health, with the microbiome being a complex community of microorganisms. Different niche preferences of microorganisms raise concerns about the adequacy of common sampling methods like swabbing and cyanoacrylate biopsy. In this study, we aim to contribute to a more suitable sampling strategy in acne microbiome studies.MethodsThis study involved ten mild to moderate acne patients. Three sampling methods were used: swab sampling (S1), modified standardized skin surface biopsy (S2), and individual comedo extraction (S3). DNA was extracted and sequenced to analyze the microbiome data.ResultsThere were significant differences in the bacterial and fungal microbiome data obtained by the three different sampling methods. Staphylococcus spp. (significantly higher in S3, P<0.05) and Malassezia spp. (higher in S3, P<0.05) were most affected by sampling methods. Bacterial phyla Proteobacteria (abundant in S1) and Bacteroidota (dominant in S2) also showed method-dependent variations.ConclusionThe choice of sampling method significantly impacts microbiome data, highlighting the need for accurate sampling to understand the relationship between the skin microbiome and acne. Standardizing sampling methods in future studies is essential for advancing skin microecology research.Clinical trial registrationhttp://www.chictr.org.cn, identifier ChiCTR-CPC-17012398.